The systematic significance of the fruit and seed morphology and anatomy in selected Oxalis L. (Oxalidaceae) species - Obone, Charline (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2005.